KEPERCAYAAN TERHADAP MISINFORMASI DAN BERITA PALSU: ANALISIS PENGARUH KUALITAS VIDEO DAN CARA BERPIKIR DENGAN METODE EKSPERIMEN - Hikmawan, Muhammad Harits; Aribowo, Muhammad Fadeel; Amrina, Yusri (Jurnal Ilmiah Penelitian Psikologi, 2023)
Social media is currently the main source of information for internet users. However, information on social media is often contaminated with misinformation and fake news. The popularity of video-based social media has exacerbated this problem. Misinformation in the form of video is easier to believe and spread than in other formats. Previous research has shown that the quality of the video influences the trust people place in the content. Similarly, the way people process information is either intuitive or analytical. This study aims to measure the effect of content quality on trust in misinformation using an experimental method. It also analyses the effect of cognitive style on trust in misinformation. The experiment was conducted with 62 participants divided into two experimental levels: level 1 shows good quality videos (stable, 720p resolution, and good lighting) and level 2 shows poor quality videos (unstable, 240p resolution, and poor lighting). Cognitive styles are measured with an adapted 5-item cognitive reflection test. As the data did not meet the normality assumption, robust regression using R software was used for data analysis. The results of the data analysis showed that both video quality and cognitive style had no significant effect on this study (p = 0.7375). In addition, the Mann Whitney U-Test on the two experimental levels also showed insignificant results (U = 446,000, p = 0.618). Therefore, it can be concluded that in this study, both cognitive styles and video quality did not significantly affect trust in misinformation or fake news.